Czech Republic : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2015)
The economy is growing strongly on account of improving domestic demand and robust exports. Fiscal policy has been supportive of the recovery and the authorities' medium-term fiscal objective is appropriate, but fiscal framework legislation that would anchor policy is yet to be approved. The central bank's use of an exchange rate floor as an additional instrument to achieve its inflation objective, in the context of the inflation- targeting framework, has helped stem deflationary pressures, but inflation is still well below target. The financial system is sound and resilient to shocks. The challenge for the authorities is to safeguard macroeconomic stability and create conditions for strong and sustainable growth. Policy recommendations. -- Fiscal policy. Maintain a supportive fiscal stance this year, but embark on a modest and very gradual fiscal consolidation thereafter, consistent with the medium-term deficit objective. Embed this objective in a comprehensive framework to enhance its effectiveness in anchoring fiscal policy. Improve budget composition, with higher capital spending to address infrastructure needs offset by efficiency gains in current expenditure and improved revenue administration. -- Monetary policy. Continue to focus on inflation targeting in policymaking and communication, and maintain supportive monetary conditions until deflation risks recede and inflation expectations become entrenched around the inflation target. Consider carefully the timing and mechanics of the eventual normalization of monetary policy. -- Financial sector. Remain vigilant and be ready to address possible risks to financial stability. -- Structural reforms. Remove impediments to higher potential growth, including through policies to increase labor market participation of certain segments of the population, enhance investment in human and physical capital, and improve the business climate.